Role and influence of federal control (supervision) on ensuring labour and equipment safety at the current stage of economic development (on the example of the Omsk region) - Yu. V. Baranov (Омский научный вестник: Серия "Общество. История. Современность")
The article considers the current state of control over labour and equipment safety implemented by such federal executive authorities as Rostechnadzor and Rostrud and their role in ensuring labour and equipment safety. As a result, common aspects in the implementation of control and supervisory activities have been identified and the decrease in the influence of federal control (supervision) has been determined on the background of a moratorium on planned inspections. In this relation, recommendations on reorganization of the existing system of control (supervision) over labour and equipment safety are proposed.